Taxonomy of cyanobacteria: a contribution to consensus approach - Palinska, Katarzyna A; Surosz, Waldemar (Hydrobiologia, 2014)
Diversity of Cyanophyceae/cyanobacteria is expressed by their morphological, biochemical and physiological properties, which enable them to settle and persist in a wide range of habitats. Their diverse morphology determined their taxonomic distinction based on phenotypic properties. The oxygenic photosynthesis which characterizes cyanobacteria and their sharing of ecological niches with eukaryotic algae, prompted their treatment in the phycological circles, where they were called blue-green algae, although their prokaryotic nature, akin to bacteria, has been recognized for over a century. The cyanobacteria are named under Botanical and Bacteriological Codes, and the usage of both systems at the same time causes considerable confusion as the rules of the Botanical Code are quite different from those of the Bacteriological one. Herbarium collections are perfect subjects for intensive phylogenetic studies and therefore can contribute to discussions on the traditional and newly emerging concepts of species and speciation in prokaryotes. This article reviews the present status of the taxonomy of cyanobacteria, describes earlier, classical and recent taxonomic approaches and the trends for future, emphasizing improvements in methodology as major catalysts for the progress of this field.